Gait analysis : an introduction - Whittle, Michael. 4 0 16; 5 (Edinburgh ;;New York : Butterworth-Heinemann, 2007)
Gait analysis is the systematic study of human walking. This book aims to bring gait analysis out of the ivory tower of the research laboratory and put it where it belongs, in the real world of the clinic.
Basic sciences --;Normal gait --;Pathological and other abnormal gaits --;Methods of gait analysis --;Applications of gait analysis --;Gait assessment in cerebral palsy --;Gait analysis data on CD-ROM.
Includes bibliographical references and index.
System requirements for accompanying CD-ROM: Windows only.
Keywords: 2 -- 0; 6; Gait.;Gait in humans. -- 20; 20; 2